Letter to Jane Tolmach from Joseph R. Cerrell - Joseph R. Cerrell:::::: (1960)
A letter explaining that more money has been transferred to the Democratic State Central Committee. And would like Tolmach to response to some rallies, conventions and receptions coming up.